UNDERSTANDING THE LINK BETWEEN CSR INITIATIVES AND CONSUMER PERCEPTION: A STUDY ON AWARENESS AND IMPACT - Bhogekar, Bipin (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study is based on the relationship between customers perceptions and Corporate Social Responsibility (CSR) programs and with a major emphasis on CSR awareness and its effects on brand loyalties, acquisition preferences and consumer trust. A standard questionnaire to 250 customers were developed to gather information on awareness of CSR initiatives and the related practices. The theories were tested on the basis of the following statistical methods: ANOVA, chi-square and Pearson correlation. The results indicate that there is a high correlation between consumers trust and CSR awareness, CSR and brand loyalty and purchasing decision. In addition, it was revealed that CSR awareness had demographic variables of age and education in its influence. According to reports, to build trust and loyalty, companies should focus on increasing CSR knowledge, particularly in the case of younger and better-educated consumers, who are of extra importance when it comes to CSR initiatives that have to shape consumer attitudes.